Comparative Economics of Traction Energetics in Arid Areas of Western Rajasthan - Kalla, Jagdeesh C; Joshi, B R; Goyal, Doulat (Annals of Arid Zone, 2016)
Economic analysis of alternative traction inputs needed for agricultural sector in the arid region of western Rajasthan revealed that supply of the total traction energy from animals as well as from machines is incommen-surate with its demand in the region. In comparative terms, the annual traction would be cheaper strictly in an ’out-of-pocket’ sence. Taking long range implications, mechanised traction seems to have an edge over the animal traction resources. A judicious combination of both animal and mechanical traction inputs is needed for better resource utilization and optimum agricultural production.